Protective effects of blueberry anthocyanin extracts on hippocampal neuron damage induced by extremely low-frequency electromagnetic field - Xiyun Sun; Zihan Xu; Yuehua Wang; Ning Liu (Food Science and Human Wellness)
The protective effects of blueberry anthocyanin extracts against damage induced by extremely low-frequency electromagnetic field (ELF-EMF) were investigated in a rat model. Wistar rats were exposed to ELF-EMF with or without the administration of blueberry anthocyanin extracts (50, 100, and 200 mg/kg per day intragastrically once a day) for 30 days. Blueberry anthocyanin extracts supplementation inhibited the decrease in Nissl substance levels, cell membrane integrity, and mitochondrial membrane potential induced by ELF-EMF; prevented the increase in nitric oxide, malondialdehyde, and Ca2+ concentrations; suppressed superoxide dismutase and glutathione depletion; and enhanced the cognitive ability of the rats exposed to ELF-EMF. The protective effects of blueberry anthocyanin extracts against hippocampal neuron injury caused by ELF-EMF were dose-dependent. These results demonstrated that blueberry anthocyanin extracts suppress hippocampal neuron injury caused by ELF-EMF by inhibiting cell membrane damage and oxidative stress pathways, and suggested that blueberry anthocyanin treatment potentially prevents hippocampal neuron injury.